1991
DOI: 10.1111/j.1365-2796.1991.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary vitamin K on warfarin‐induced anticoagulation

Abstract: We examined the effect of vitamin-K-rich vegetables, vitamin-K-poor vegetables and phytomenadione on the stability of warfarin-induced anticoagulation. Patients on stable anticoagulant treatment were randomized to either 1 (n = 5), 2 (n = 7) or 7 (n = 13) d with high intake of vitamin-K-rich vegetables (median daily vitamin K intake 1100 micrograms) or high intake of vitamin-K-poor vegetables (daily vitamin K intake 135 micrograms) for 6 d (n = 7), or habitual diet supplemented with 1000 micrograms of phytomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 3 publications
2
64
0
2
Order By: Relevance
“…However, since the activation of thrombin is inextricably linked with the vitamin K cycle in the coagulation cascade, there is the possibility that the pharmacological activity of direct thrombin inhibitors could be influenced by alterations in vitamin K availability. The enhanced pharmacological activity of warfarin in vitamin K deficient rats observed in this study confirms the well-established impact of vitamin K deficiency on anticoagulation response to warfarin in man [4][5][6][8][9][10]. This study also demonstrates that overt vitamin K deficiency enhances the anticoagulant activity of the direct thrombin inhibitor, ximelagatran, in rats.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, since the activation of thrombin is inextricably linked with the vitamin K cycle in the coagulation cascade, there is the possibility that the pharmacological activity of direct thrombin inhibitors could be influenced by alterations in vitamin K availability. The enhanced pharmacological activity of warfarin in vitamin K deficient rats observed in this study confirms the well-established impact of vitamin K deficiency on anticoagulation response to warfarin in man [4][5][6][8][9][10]. This study also demonstrates that overt vitamin K deficiency enhances the anticoagulant activity of the direct thrombin inhibitor, ximelagatran, in rats.…”
Section: Discussionsupporting
confidence: 87%
“…Warfarin causes anticoagulation by inhibiting the reductase enzymes, which generate vitamin K hydroquinone from vitamin K epoxide in the liver, thus preventing activation of the clotting proteins [7]. The availability of vitamin K thus plays a role in determining the effectiveness of warfarin, and dietary modification by either lowering or increasing vitamin K intake can increase or decrease patients' sensitivities to the drug [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in dietary intake of vitamin K can have a significant effect on anticoagulation response to oral anticoagulants; increases in the dietary intake of vitamin K are associated with significant reductions in anticoagulation response, 6,9,[12][13][14][15] whereas the opposite causes warfarin sensitivity. 6,12 Earlier we showed that in patients with stable control of anticoagulation, for every 100-g increase in vitamin K intake in the previous 4 days, INR falls by 0.2, 16 further exemplifying the relationships between dietary vitamin K and anticoagulation response.…”
Section: Discussionmentioning
confidence: 99%
“…12 Current information comes from sporadic case reports, mostly documenting a resistance to OACs from increased intakes of vitamin K-rich foods 13,14 or supplements 15,16 or from limited experimental studies in patients. 17,18 Here, we report a systematic vitamin K dose-response study in 12 young healthy adults who had been initially stabilized with acenocoumarol for 4 weeks to a target INR of 2.0. Although this target INR is at the low end of the target ranges for most short-term (full-dose) OAC regimens, it is at the upper end of the target INR of 1.5 to 2.0 used in the recent, and highly successful, long-term trial using low-intensity warfarin to prevent recurrent venous thromboembolism.…”
Section: Introductionmentioning
confidence: 99%